Carriage and potential long distance transmission of Listeria monocytogenes by migratory black-headed gulls in Dianchi Lake, Kunming. Issue 1 (1st January 2019) - Gan, Lin; Cao, Xiaolong; Wang, Yan; Wang, Yiqian; Jiang, Huaying; Lan, Ruiting; Xu, Jianguo; Ye, Changyun
ABSTRACT: Listeria monocytogenes is a high risk pathogen which can cause invasive diseases in humans. We previously reported that black-headed gulls from Dianchi Lake of Kunming carrying L. monocytogenes, while the characteristics of these isolates and the relationship with habitats of migratory gulls have not been explored. In this study, we investigated the prevalence and molecular characteristics of Listeria monocytogenes from black-headed gulls in Dianchi Lake, and phylogenetic analysis based on core genome SNPs was used to determine the genetic relationship of the strains from Dianchi Lake and other regions. Occurrence of L. monocytogenes in black-headed gull feces in 2016, 2017 and 2018 was 1.0%, 1.0% and 0.6% respectively. The predominant serotype of 28 isolates was 4b, while the predominant sequence types were ST145 and ST201. Based on their prevalence and genomic relationships, ST5 and ST87 were likely to be sourced locally while ST145 and ST201 were likely to be non-local. L. monocytogenes may travel along the bird migration route leading to transmission over a large geographical span carried by black-headed gull. Although the prevalence of L. monocytogenes was low, its carriage by the migratory black-headed gulls poses potential public health risks in regions where the migratory birds passage and reside.